NQO1 antagonizes PM2.5-induced apoptosis of Sertoli cells by activating the UPRmt pathway - Cao Wang; Qing Xiao; Mingchen Xiao; Yu Chu; Yaya Ai; Zhen Luo; Guangxu Zhou; Kaiyi Mao; Bin Liu (Ecotoxicology and Environmental Safety, 2025)
The mechanism by which NQO1 antagonizes PM2.5-induced apoptosis in Sertoli cells through activation of the mitochondrial unfolded protein response (UPRmt) was investigated. A reproductive toxicity model was established using TM4 cells exposed to PM2.5 (50 μg/mL, 24 h). Transcriptome sequencing and bioinformatics analysis identified NQO1 as the target gene, playing a key role in redox regulation and apoptosis. Phenotypic analysis showed that PM2.5 exposure significantly increased intracellular ROS levels (P < 0.01), induced structural disintegration of mitochondrial cristae (as observed by TEM), and activated apoptosis pathways. Overexpression of NQO1 effectively mitigated these effects. The mechanistic analysis demonstrated that NQO1 overexpression significantly upregulated UPRmt-related proteins (HSP60, ATF5, and CLPP) (P < 0.05), increased SOD activity, and reduced MDA levels (P < 0.01). On the other hand, NQO1 knockout led to mitochondrial membrane potential loss and Cytochrome C release via UPRmt inhibition (P < 0.01), resulting in an increased Bax/Bcl-2 ratio and enhanced apoptosis. Overall, these findings suggest that the NQO1-UPRmt axis protects against PM2.5-induced germ cell damage by maintaining mitochondrial protein homeostasis and redox balance. This study identifies potential therapeutic targets for male infertility associated with environmental pollutants.